Education and Training on the Utilization of Barangan Banana Peel into Liquid Soap as Home Industry in Siguci Village, North Sumatra - Maha, Hetty Lendora; Anayanti Arianto; Sony Eka Nugraha; Jane Melita Keliat (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Indonesia one of country that is rich in natural plants that have an active compounds and are used by some people as active substances in the world of cosmetics such as soap. During this time, people only use bananas, limited to the use of the fruit, then the banana’s peel after consumption is only disposed of as waste. Several previous studies have stated that musa acuminata peel contain saponins, flavonoids, alkaloids and tannins. Based on the description, that musa acuminata peel can be used as a antibacterial’s liquid soap. One of the musa acuminata producing areas in North Sumatra is Siguci Village, Deli Serdang Regency. The method used in this service are presentation about musa acuminata, their benefits, the active compounds they contain and the utilization of the waste of musa acuminata peels, as well as providing material on marketing techniques for home industry products. The results of this activity showed that as many as 20 residents were understands and is able to produce liquid soap made from musa acuminata peels, and can make attractive packaging., which can be seen from the results of the pre-test and post-test that were carried out during the educational activity.